Efforts To Increase Teachers' Competence In Developing Rpp And Syllabus Through Sustainable Academic Supervision At SDN 017 Muara Material Singingi Hilir District - Sriyanto Ramelan Sutoyo (STKIP Rokania Pasir Pangaraian, 2021)
study This to determine the improvement of teacher competence in preparing lesson plans and syllabus through supervision. This research was conducted in two cycles. The results of the analysis in the 2019 school year at SD Negeri 017 Muara Bahan Kec. Singingi Hilir, the problem arises is the lack of teachers who make lesson plans, especially the preparation of syllabus and lesson plans. To examine the weak performance of teachers in this regard, a study was conducted to see the extent to which the principal's academic supervision measures can improve teacher competence in the preparation of syllabus and lesson plans. As for the results obtained from this research, continuous academic supervision is scientifically proven to improve teacher competence in compiling syllabus and lesson plans at SD Negeri 017 Muara Bahan Kec. Singingi Downstream. This is evidenced by the increasing number of good teacher syllabuses from 30% to 90% after academic supervision. In addition, the number of good quality lesson plans also increased from 30% to 90%